Effect of Thrombopoietin Receptor Agonist on Pregnant Mice - Kensaku Nakai; Takuya Misugi; Kohei Kitada; Yasushi Kurihara; Mie Tahara; Akihiro Hamuro; Akemi Nakano; Masayasu Koyama; Yukimi Kira; Daisuke Tachibana (MDPI AG, 2022)
Thrombopoietin receptor agonists (TPO-RAs) are an effective treatment for refractory immune thrombocytopenia (ITP). However, the use of TPO-RAs is limited for ITP in pregnant women due to concerns about fetal toxicity. In this study, we examined the effects of romiplostim, one of the TPO-RAs, on pregnant mice. The mice were injected subcutaneously with romiplostim (1, 5, 10, 30, and 100 μg/kg) on gestational days (GD) 1, 8, and 15. We evaluated maternal and fetal platelet and megakaryocyte counts (MK), fetal weight at birth, placental morphology, and miscarriage rates. Romiplostim increased platelet and MK counts in pregnant mice at all doses and in fetuses at doses above 10 µg/kg. Fetal weight at birth was slightly reduced at a dose of 100 μg/kg, but there were no significant differences in placental weight, spiral artery wall thickness, placental growth factor signal changes, or the rate of resorption at that dosage. The dose of romiplostim used clinically for ITP patients (1-10 μg/kg) did not show any adverse effects on pregnant mice. Although the results of the present study are encouraging, until there are more conclusive data, the use of romiplostim should be evaluated individually in severe, life-threatening cases, and all relevant ethical aspects should be considered.